Mass incarceration in the 21st century: realities and reflections - Conyers, Addrain; Lynn, Vanessa; Leigey, Margaret E. (Routledge, 2024)
"This reader presents a comprehensive review of the research on mass incarceration as it relates to causes, impact, and solutions. Assembling contributions from leading experts in a variety of disciplines as well as the voices of directly impacted people, the editors have created a diverse collection of chapters addressing prison, punishment, incarceration, reentry, and reintegration embedded in the context of the ever-evolving discussion around ending mass incarceration. The effects of the exponential prison growth in the United States over more than 50 years have been catastrophic, resulting in disparities that especially plague the poor, communities of color, and women. Mass incarceration is a culmination of policies and practices that benefit the privileged praxis and consequently disproportionally disenfranchise marginalized communities. The ideology affects every stage of the criminal justice system, from policing to release, and this book meets the need to expand the examination beyond departments of corrections to explore the administration behind laws, biased practices, and an unforgiving societal stigma. It deepens comprehension and engagement with concise and accessible readings that offer nuance and provoke thought. The book is ideal as a primary or supplementary textbook for corrections, prisons, or penology courses, as well as courses focused on law, policy, sociology, social work, and social justice. It also will serve as a valuable reference book for any individual searching for knowledge on the past, present, and future of mass incarceration"--